Investigation of the thermo-optical behavior of multicore fibers used in coherently combined fiber laser systems - Steinkopff, Albrecht; Jauregui, Cesar; Klenke, Arno; Aleshire, Christopher; Tuennermann, Andreas; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
In this work we present theoretical investigations of the power scaling potential of multicore fibers. In principle it is widely accepted that increasing the number of active cores helps to overcome current challenges such as transversal mode instabilities and non-linear effects. However, in order to do a proper analysis of the average power scaling potential of multicore fibers it is required to pay particular attention to thermal effects arising in such fibers. Therefore, a simulation tool has been developed that is capable of solving the laser rate equations, taking into account the resulting temperature gradient and the distortions in the mode profiles that it causes. In the study several different multicore fibers possessing a rectangular core position layout of 2×2 to 7×7 of active cores have been analyzed. Moreover, we have investigated the influence of the active core size in terms of thermal effects as well as the extractable output power and energy. This includes a study in the maximum achievable coherent combination efficiency of the multicore channels (that is strongly influenced by the distorted mode profile at the fiber end facet), the impact on nonlinear effects, the optical path differences between the cores and the amplification efficiency which are all triggered by thermal effects. Finally the scaling potential as well as the challenges of such fibers will be discussed.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Coherent combining; Multicore fiber; Thermo-optical behavior